Modeling flexible manufacturing systems: the concurrent logic programming approach - Dotan, Y.; Ben-Arieh, D. (IEEE transactions on robotics and automation, 1991)
A novel approach to the modeling and analysis of an FMS (flexible manufacturing system) is presented, focusing on shop-floor control processes. This approach is based on concurrent logic programming, which uses the theoretical foundation of communicating sequential processes and guarded commands with nondeterminacy. The modeling approach is implemented using Flat Concurrent Prolog (FCP) on a Sun workstation or on a VAX machine. The properties of concurrent logic programming, as demonstrated by using FCP, include: (1) hierarchical description; (2) support for timing specifications; (3) modeling of concurrency and synchronization; (4) support for generic modeling; (5) facilitation of data transfer and complex communication; (6) capability of performance evaluation; (7) capability of static and dynamic analysis; (8) debugging capabilities; and (9) simulation ability.< >